Laminated Object Manufacturing of Ceramic‐Based Materials. Issue 9 (20th May 2020) - Dermeik, Benjamin; Travitzky, Nahum
Abstract : Since their inception, additive manufacturing (AM) techniques have been the go‐to methods for obtaining highly complex‐shaped rapid prototypes (RPs) and specialized parts, which were produced in small lot sizes. The AM technique of laminated object manufacturing (LOM) is an immensely convenient and cost‐effective method for quickly producing millimeter‐sized to meter‐sized parts, while incorporating micrometer‐sized constructive features. LOM machines offer an open work space, within which nontoxic and highly filled sheet materials can be processed at a high production velocity. The unique property profile of ceramic‐based materials from LOM may be indispensable for applications calling for materials that unite high temperature resistance, mechanical strength, and light weight. Optionally, local material functionalization may engender the electrical conductivity, chemical stability, ferroelectricity, radiation shielding, or filter membrane stability of a limited portion of the material. Herein, a detailed evaluation of the applicability of LOM in the near net shaping ceramic‐based materials is presented. Optional technical adjustments for the LOM process and extensions of the LOM machine configuration can improve the economic feasibility its operation. Previously successful LOM‐printed ceramic‐based materials are showcased within a comprehensive overview on the state of the art and potential novel composite materials are presented. Abstract : In comparison to other additive manufacturing techniques for ceramic‐based materials, laminated object manufacturing (LOM) may be more cost efficient and time saving. Herein, a short description is presented: 1) utilization of computer‐aided design (CAD) as input data; 2) transferring of layer‐wise cutting patterns onto a continuous strand of preceramic sheet material; 3) heat treatment of LOM multilayers, yielding finished ceramic‐based materials.